2003
DOI: 10.1152/ajpheart.00407.2002
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone administration limits infarct size by reduced phosphorylation of canine myocardial connexin43 proteins

Abstract: Lee , Tsung-Ming, and Tsai-Fwu Chou. Troglitazone administration limits infarct size by reduced phosphorylation of canine myocardial connexin43 proteins. Am J Physiol Heart Circ Physiol 285: H1650-H1659, 2003 10.1152 10. / ajpheart.00407.2002 antidiabetic thiazolidinedione, has been shown to have a scavenging effect on reactive oxygen species, which can modulate expression of connexin43. The study purpose was to evaluate whether troglitazone provides cardioprotection and to assess whether the cardioprotection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…In addition to the apoptotic component of cell death contributing to the extension of infarct size during reperfusion, Zhao et al (18) demonstrated that pharmacologic inhibition of the reperfusion-induced apoptotic component of cell death also resulted in improved contractile function of ischemic canine hearts. In healthy, diabetic, or obese animals, PPARγ agonists reduced the size of myocardial infarcts (19). These effects are associated with increased uptake of glucose and improved sensitivity to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the apoptotic component of cell death contributing to the extension of infarct size during reperfusion, Zhao et al (18) demonstrated that pharmacologic inhibition of the reperfusion-induced apoptotic component of cell death also resulted in improved contractile function of ischemic canine hearts. In healthy, diabetic, or obese animals, PPARγ agonists reduced the size of myocardial infarcts (19). These effects are associated with increased uptake of glucose and improved sensitivity to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms through which PPARs have been shown to inhibit NF-jΒ signaling include decreased protein kinase activation such as ERK1/2, JNK, Akt, and GSK3b [68, 118,119] and regulation of the expression of the inhibitor IjBa [120,121]. In addition, activated PPARb/d has been shown to release the co-repressor Bcl-6 to exert its antiinflammatory actions [122,123]. However, it is not clear yet whether this mechanism is relevant for the anti-inflammatory effects of PPARs in cardiac myocytes.…”
Section: Ppars In Inflammatory Responsementioning
confidence: 99%
“…In normal or insulin-resistant rodents, treatment with PPAR-␥ activators improved contractile recovery and/or reduced infarct size after ischemia and reperfusion (140)(141)(142)(143)(144)(145)(146)(147)(148)(149). Intravenous troglitazone reduced myocardial infarct size in dogs ( 150 ). Chronic, oral troglitazone suppressed infl ammatory responses and improved postischemic contractile function in pigs ( 151 ), but the protective effects of troglitazone may have been due to its ␣ -tocopherol moiety rather than PPAR-␥ activation, as treatment with equimolar by guest, on www.jlr.org Downloaded from cardiovascular outcomes ( 92,187 ).…”
Section: Ischemia/reperfusion Injurymentioning
confidence: 99%
“…In vivo studies indicate a potential for TZD drugs to infl uence cardiac arrhythmias. In dogs, troglitazone promotes dephosphorylation of connexin 43, a gap junction protein, in response to ischemia and reperfusion ( 150 ), an effect with possible pro-arrhythmic consequences. In pigs, acute treatment with troglitazone, rosiglitazone, or pioglitazone, resulting in clinically relevant plasma concentrations, blocks cardiac ATP-sensitive potassium (K ATP ) channels, promotes ischemic ventricular fi brillation, and impairs the success of defi brillation ( 24,26 ).…”
Section: Ion Channels and Electrophysiologymentioning
confidence: 99%